Pathways to Early Retirement: The determinants and motivational drivers - MAT RAZALI, NUR NADIAH SALIHAH; Fernando, Yudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
Embarking on early retirement commences with a deliberate preference for leaving the workforce ahead of schedule. This choice is sustained by clear intentions to retire early and ultimately culminates in adapting to the novel life stage that arises from the permanent withdrawal from employment. Early retirement employs the theoretical constructs of ‘push’, ‘pull’, and ‘jump’ to elucidate the factors precipitating early retirement. ‘Push’ factors are identified as the consequences of adverse health conditions and involuntary job terminations, ‘pull’ factors are recognized as the economic and symbolic incentives provided by the welfare state, and ‘jump’ factors are characterized by the proactive pursuit of new life ventures or enhanced familial engagement, such as spending more time with grandchildren. Using Theory of planned behavior (TPB), the objectives of this study are to examine factors contributing to individual’s early retirement by planning their retirement. The findings indicate that positive attitudes toward retirement, social influences from subjective norms, and a strong sense of perceived behavioral control are pivotal in shaping individuals’ intentions to retire early. Furthermore, the perceived financial knowledge and perception of health significantly enhances proactive retirement planning behavior, which subsequently influences retirement decisions. By integrating these factors into a conceptual framework, this paper contributes to the expanding body of knowledge on retirement planning and lays the groundwork for future research aimed at empirically validating these relationships and supporting effective retirement planning interventions.